New and Old Routes of Portuguese Emigration Uncertain Futures at the Periphery of Europe - Pereira, Cláudia; Azevedo, Joana; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This open access book offers a comparative overview on Portuguese emigration in Europe and outside the EU in times of recession. It looks at Portuguese emigrants who, after the crisis of 2008, moved both intra-EU, such as UK, France, Switzerland, Germany and Spain, but also into countries with historical links, such as the USA and Canada, and to Portuguese speaking countries such as Brazil, Angola and Mozambique, as well as the processes of return. In addition to the dynamics of movement, the book provides an in-depth analysis of the heterogeneity of this emigration. It deepens the multifaceted identities concerning social and professional pathways among highly skilled and less skilled emigrants. The labour market continues to be the main regulatory force of Portuguese emigration, which helps to explain the outflow and the processes of settlement and return. Nonetheless, this book demonstrates that non-economic factors have likewise been of great importance in the decision to emigrate. As such this book will be a valuable read to policy makers, students and scholars in migration.
1. The Fourth Wave of Portuguese Emigration: Austerity Policies, European Peripheries and Postcolonial Continuities: Cláudia Pereira and Joana Azevedo -- Part I New Patterns of Portuguese Emigration: a Broad Perspective : 2. Portuguese Emigration Today: Rui Pena Pires -- 3. New Emigration and Portuguese Society: Transnationalism and Return: João Peixoto, Pedro Candeias, Bárbara Ferreira, Isabel Tiago de Oliveira, Joana Azevedo, José Carlos Marques, Pedro Góis, Jorge Malheiros, Paulo Miguel Madeira, Aline Schiltz, Alexandra Ferro and Eugénio Santana -- 4. Portuguese Emigrants' Political Representation: the Challenges of the External Vote: Marco Lisi, Ana Maria Belchior, Manuel Abrantes and Joana Azevedo: Part II The Labour Market and Portuguese Emigration: Highly Skilled and Less Skilled Migrants: 5. A New Skilled Emigration Dynamic: Portuguese Nurses and Recruitment in the Southern European Periphery: Cláudia Pereira -- 6. Migrating to Complete Transitions: a Study of High-Skilled Youth Migration to France João Teixeira Lopes -- 7. 'Pulled' or 'Pushed'? The Emigration of Portuguese Scientists: Ana Delicado -- 8. Working Class Condition and Migrant Experience: the Case of Portuguese Construction Workers: João Queirós -- 9. Entrepreneurship Among Portuguese Nationals in Luxembourg: José Carlos Marques -- Part III Portuguese Emigrants: Postcolonial Continuities: 10. Contemporary Portuguese Migration Experiences in Brazil:Old Routes, New Trends: Marta Vilar Rosales and Vânia Pereira Machado -- 11. Portuguese Emigration to Angola (2000-2015): Strengthening a Specific Postcolonial Relationship in a New Global Framework?: Pedro Candeias, Jorge Malheiros, José Carlos Marques, Ermelinda Liberato -- Part IV Portuguese Emigrants: Identities: 12. "I Was Enthused When I 'Returned' To Portugal, But I'm Leaving Disillusioned": Portuguese Migrant Descendant Returnees from Canada and Narratives of Return, Re-Return And Twice Migration: JoãoSardinha -- 13. An Immigrant in America Yes, But Not an Emigrant in My Own Country! The Unbearable Weight of a Persistent Label: Graça Índias Cordeiro -- Part V Final Reflections: 14. New Migration Dynamics on the South-Western Periphery of Europe: Theoretical Reflections on the Portuguese Case: Russell King.
Keywords: Emigration and immigration; Population -- Economic aspects; Political science; Human Migration; Population Economics; Political Science